Cimento de ionômero de vidro é melhor do que resina composta em restaurações classe II de dentes decíduos? Uma revisão sistemática com meta-análise. - Dias, Ana Giselle Aguiar [UNESP] (2016)
The aim of the present study was to perform a systematic review and meta analysis (MA) on the clinical performance of glass ionomer cement (GIC) compared to composite resin (CR) in class II restorations in deciduous teeth. A comprehensive search was performed on the PubMeb, Scopus, Web of Science, LILACS BBO, Cochrane Library, Clinical Trials and OpenGrey databases, without dat e or language restrictions. Mesh terms, synonyms and key words were used, adapted for each database. Manual search was also performed on the list of references of the selected articles. Five randomized controlled trials and three non randomized clinical tr ials comparing the clinical performance (assessed by the presence of secondary caries lesions, marginal discoloration, marginal adaptation, anatomical shape, and retention and wear of restorative material) were included in class restorations II performed w ith GIC compared to RC restorations in deciduous teeth. Fifteen complete studies were read in full, of which 8 were included in qualitative (risk of bias) and quantitative synthesis (meta analysis). The heterogeneity ranged from low to moderate in the 12 M As from the 8 studies, with a follow up of 6 to 48 months (38 to 73%), with no significant difference between the two materials in the final analysis (overall effect). The risk difference (95% confidence interval, p value) between RC and GIC for failure wa s 0.03 ( 0.11 0.05; p = 0.41); for marginal adaptation was 0.01 ( 0.06 0.05; p = 0.8); for marginal discoloration it was 0.07 ( 0.11 0.26, p = 0.44), and for the anatomical form it was 0.00 ( 0.04 0.05; p = 0.84). Regarding the presence of seconda ry caries lesion, the corresponding value was 0.07 (0.02 0.12; p = 0.01). The overall risk difference for clinical performance was 0.03 ( 0.01 0.06, p = 0.17). For all the analyzed parameters, the exclusion of the studies with less than 24 months of fo llow up and the exclusion of non randomized studies did not influence the final result of the MA. However, the results were significantly influenced by the type of GIC (conventional or resin modified) and type of isolation (absolute or relative). It was co ncluded that resin modified GIC presented a clinical performance significantly higher than RC in relation to the prevalence of secondary caries lesions, whereas conventional GIC was similar to RC for this parameter. Regarding the whereas conventional GIC was similar to RC for this parameter. Regarding the percentage of marginal faipercentage of marginal failure, marginal adaptation, marginal discoloration and lure, marginal adaptation, marginal discoloration and anatomical shape, both materials presented similar performance, regardless of the anatomical shape, both materials presented similar performance, regardless of the type of GIC. Thus, the possibility of light curing along with its cariostatic properties, type of GIC. Thus, the possibility of light curing along with its cariostatic properties, indicate that resinindicate that resin--modified Gmodified GIC is the material of choice for class II restorations in IC is the material of choice for class II restorations in deciduous teeth.deciduous teeth.